El nenúfar más grande del mundo: Victoria amazónica - Flores Rengifo, Raziel Onirys (2024)
This research work aims to propose a ready-towear men’s collection with a streetwear style based on the theoretical and visual analysis of the Amazonian Victoria. A deep research on the Amazonian Victoria was developed, describing its main characteristics and origin. The user of the proposed collection are young men between 25 to 35 years old who appreciate fashion, as it is their way to express themselves and stand out from the crowd. The conceptual element of the collection is transformation, which encompasses the idea of the process of evolution and pollination of the Amazonian Victoria. The concept is reflected in both textures and colors. An interview was conducted with the Peruvian designer and director of the Art, Fashion and Textile Design career at the Pontificia Universidad Católica del Perú for his knowledge of streetwear garments and textile printing. On the other hand, creative and fashion references were established for the visual development of the project. In addition, textile research and prototype experimentation were carried out to contribute to the creative design process. The result is a collection composed of 15 outfits, which take as inspiration the colors and textures of the leaves and flowers of the Amazonian Victoria.